Synthesis of SiO2/TiO2 Core – Shell Nanofibres for Photodegradation of Hexamethyldisiloxane - Kamba, E. A.; Daniel, E. B Attah (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
As the world faces the increasing energy demands of its growing population a number of novel and renewable energy sources are being investigated as replacement agents for conventional fossil fuel species. In this study SiO2/TiO2 core–shell nanofibres were synthesised and characterised using facile experimental procedures. The synthesized catalyst was utilized for photodecomposition of hexamethyldisiloxane (HMS) in biogas. The results obtained revealed that by the decomposition properties of the created material it was possible to establish a photocatalyst equipped with properties capable of decomposing siloxanes in biogas with high efficiency.